Stoicism and Verbal Aggression in Serial Arguments: The Roles of Perceived Power, Perceived Resolvability, and Frequency of Arguments - Johnson, Elle P. (Journal of interpersonal violence, 2022)
Impelled by a desire to control, suppress, and deny emotional response, stoic individuals may act out their pent-up emotions on relational partners by provoking conflict and/or engaging in partner-directed violent and aggressive behaviors. However, little is known regarding what factors can push stoics over the edge from remaining quiet or avoiding revealing frustrations to initiating aggressive behavior. This relationship between stoicism and aggression is important to consider in serial arguments, where the repetitive nature of a conflict may become increasingly difficult for stoics to manage internally. Here, we examined the influence of stoicism on verbal aggression in serial arguments between romantic partners. We additionally considered the effects of power, perceived resolvability, and argument frequency on the relationship between stoicism and verbal aggression. Using a survey design with a sample of 281 individuals involved in a romantic relationship, we observed that stoicism is positively associated with verbal aggression in serial arguments. While perceived power and resolvability did not moderate the relationship between stoicism and verbal aggression, argument frequency about a serial argument topic was a significant moderator. The results of this study imply that stoicism plays an important role in explaining aggressive tactics in conflict. A high argument frequency about a conflict topic may lead to a buildup of unexpressed emotions, particularly anger, in stoic individuals, resulting in an explosive release of violence and aggression toward a romantic partner. Unique results on the relationship between stoicism and power and directions for future research are discussed.